1965
DOI: 10.1113/expphysiol.1965.sp001780
|View full text |Cite
|
Sign up to set email alerts
|

The Hemoglobin, Oxygen, Carbon Dioxide and Hydrogen Ion Concentrations in the Umbilical Bloods of Sheep and Goats as Sampled via Indwelling Plastic Catheters

Abstract: A method is described for the introduction of plastic catheters into the umbilical vessels of fetal goats and lambs whereby samples of blood may be obtained over a period of days and weeks in conditions in which the mother is free from obvious stress. The results of the analyses of samples so obtained, indicate that (1) the oxygen capacity of the fetal blood does not increase after 100 days and (2) that the oxygen saturation does not fall systematically in the last month of gestation. Data on the day to day va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

1967
1967
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 5 publications
7
60
1
Order By: Relevance
“…The ewe was placed on her back and the Uterus exposed through a mid-line abdominal incision. The umbilical vessels were catheterised by COMLJNE and SILVER'S [2] modification of the method used by MESCHIA et al [28]. The cord was located by palpation through a 2-3 inch incision in the artero-median surface of the utedne wall, and small branches of one umbilical vein and an artery were cannulated with No.…”
Section: Methodsmentioning
confidence: 99%
“…The ewe was placed on her back and the Uterus exposed through a mid-line abdominal incision. The umbilical vessels were catheterised by COMLJNE and SILVER'S [2] modification of the method used by MESCHIA et al [28]. The cord was located by palpation through a 2-3 inch incision in the artero-median surface of the utedne wall, and small branches of one umbilical vein and an artery were cannulated with No.…”
Section: Methodsmentioning
confidence: 99%
“…Polyvinyl catheters (0.58 mm i.d.) were inserted in the main umbilical vessels from their peripheral branches in the two uterine horns according to techniques previously described (7,10). Satisfactory catheterization of both umbilical arteries and veins was achieved in 8 of 11 experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [5,6,10,11] have shown that stressful procedures have a significant effect on the physiologic state of the fetus. A steady state must be present at the time of sampling in order for a ratio of uptakes to be a meaningful metabolic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The catheters were brought through a subcutaneous tunnel to a flank patch as previously described [10]. The animals were standing and feeding within 6 hours of surgery.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation